Field experience of transformer untanking to identify electrical faults and comparison with dissolved gas analysis - Samsudin R.; Ramli A.Q.; Berhanuddin A.; Zaidey Y. (2023)
Power transformer consists of components which are under consistent thermal and electrical stresses. The major component which degrades under these stresses is the paper insulation of the power transformer. The life of the transformer is determined by the condition of the paper insulation. The degradation of the paper insulation will be accelerated with the presence of electrical fault. Electrical fault in power transformer can be categorized into two which are Partial Discharge (PD) and Arcing. A PD will eventually develop into arcing. Any electrical fault in the transformer can be detected by using Dissolved Gas Analysis technique. The DGA can be used to differentiate between the types of faults in the transformer. However, DGA alone is not conclusive in determining the electrical fault in the transformer. As a complement, acoustic partial discharge technique was used to detect the electrical fault in the transformer. In this paper, the detection of electrical fault in two units of 33/11kV, 15MVA transformers were done by using Dissolved Gas Analysis (DGA). Then, the acoustic partial discharge test was carried out to detect the activity and locate the source of the electrical fault. During the acoustic partial discharge testing, some electrical discharge signal was picked-up from On-Load Tap Changer (OLTC) tank. Then, the transformers were un-tanking for physical inspection. Based on the inspection done on two transformers, the DGA analysis methods were unable to detect the OLTC oil contamination in the main tank oil and it is very dependent on the transformer conservator tank design. The acoustic partial discharge technique proves to be a useful tool in detecting electrical discharges in the power transformer. 2009 IEEE.